Malaria in children and G6PD deficiency in an endemic area for malaria in Bengo province, Angola - Brito, Miguel (2019)
Glucose 6-phosphate dehydrogenase (G6PD) is the rate-limiting enzyme of the pentose phosphate pathway, important in the protection of cells against oxidative stress. The G6PD deficiency is the most common enzymopathy X linked worldwide. The majority of the G6PD deficient do not manifest any symptoms, however, acute hemolytic anemia may be trigger by several agents, such as primaquine. Current WHO guidelines state that in elimination areas a single 0.25 mg base/kg primaquine dose should be given, as a gametocytocide, to all patients with parasitological-confirmed P. falciparum malaria on the first day of treatment in addition to an ACT. In face of this recommendation, endemic malaria countries should be informed of the prevalence of G6PD deficiency, in order to make safe and appropriate decisions regarding the use of potentially unsafe drugs for G6PD deficient individuals. Objectives: The aim of this study is to determine the prevalence of G6PD deficiency in a holoendemic region in Africa for P falciparum, evaluating the genotype and the phenotype of the enzyme.